Pemberdayaan Kader melalui Edukasi Perawatan Komplementer Biomassage dalam Meningkatkan Daya Imun Tubuh Penyakit Tidak Menular pada Lansia - Ribek, Nyoman; Labir, Ketut; Suardani, Ni Luh Ketut (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background:The high number of cases of death due to cervical cancer in Indonesia is exacerbated by the arrival of sufferers to health services at an advanced stage of > 70%. Efforts can be made to reduce risk factors for cervical cancer through primary prevention efforts. Purpose:The aim of community service is to increase teenagers' knowledge and attitudes about cervical cancer, with educational methods through audiovisual media. Method: This community service is carried out through audiovisual method counseling. This activity begins with identifying knowledge and attitudes or a pre-test about cervical cancer. The activity continued with counseling using video media about preventing cervical cancer and a post test after the counseling was carried out in one room in the School. Result: The level of knowledge before education was mostly sufficient 72 people (72%) and the attitude category was sufficient 70 (70%). After education there was a good increase in knowledge from 28 (26%) to 91 people (91.0%), while attitudes also existed an increase from 5 people with good attitudes to 87 people (87%). Conclusion:It is hoped that health workers will increase educational activities using audio-visual methods about cervical cancer. The public, especially young women, are expected to seek information from print and electronic media about cervical cancer.